2017
DOI: 10.4143/crt.2016.371
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Chemotherapy in Patients with Unresectable or Metastatic Pancreatic Acinar Cell Carcinoma: Potentially Improved Efficacy with Oxaliplatin-Containing Regimen

Abstract: PurposePancreatic acinar cell carcinoma (ACC) is a rare cancer of the exocrine pancreas. Because of its rare incidence, the efficacy of chemotherapy in this patient population has been largely unknown. Therefore, we retrospectively analyzed the outcomes of patients with advanced pancreatic ACC who received chemotherapy.Materials and MethodsBetween January 1997 and March 2015, 15 patients with unresectable or metastatic pancreatic ACC who received systemic chemotherapy were identified in Asan Medical Center, Ko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 25 publications
2
48
0
Order By: Relevance
“…Small cohort studies and case reports list a number of regimens with an overall response rate of 23% and a median PFS of 5.6 mo (Al-Hader et al 2017;Yoo et al 2017). Chemotherapeutic substances include gemcitabine, capecitabine, 5-fluoruracil, irinotecan, cisplatin/oxaliplatin, and taxanes (Lowery et al 2011;Al-Hader et al 2017;Yoo et al 2017;Brunetti et al 2018) and also targeted therapies such as erlotinib or panitumumab in KRAS wild-type tumors (Morales et al 2013;Kruger et al 2016). Regarding predictors of treatment response, defects in DNA repair genes such as BRCA1, BRCA2, and PALB2 have been linked to prolonged survival following platinum-based regimens in some patients (Al-Hader et al 2017;Yoo et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small cohort studies and case reports list a number of regimens with an overall response rate of 23% and a median PFS of 5.6 mo (Al-Hader et al 2017;Yoo et al 2017). Chemotherapeutic substances include gemcitabine, capecitabine, 5-fluoruracil, irinotecan, cisplatin/oxaliplatin, and taxanes (Lowery et al 2011;Al-Hader et al 2017;Yoo et al 2017;Brunetti et al 2018) and also targeted therapies such as erlotinib or panitumumab in KRAS wild-type tumors (Morales et al 2013;Kruger et al 2016). Regarding predictors of treatment response, defects in DNA repair genes such as BRCA1, BRCA2, and PALB2 have been linked to prolonged survival following platinum-based regimens in some patients (Al-Hader et al 2017;Yoo et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapeutic substances include gemcitabine, capecitabine, 5-fluoruracil, irinotecan, cisplatin/oxaliplatin, and taxanes (Lowery et al 2011;Al-Hader et al 2017;Yoo et al 2017;Brunetti et al 2018) and also targeted therapies such as erlotinib or panitumumab in KRAS wild-type tumors (Morales et al 2013;Kruger et al 2016). Regarding predictors of treatment response, defects in DNA repair genes such as BRCA1, BRCA2, and PALB2 have been linked to prolonged survival following platinum-based regimens in some patients (Al-Hader et al 2017;Yoo et al 2017). Interestingly, the patient reported here had a germline heterozygous stop-gain mutation in PALB2, which has previously been reported in the context of familial pancreatic and breast cancer (Slater et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…There is no standard chemotherapy regime for unresectable pancreatic ACC cases. Yoo et al [ 18 ] confirmed that oxaliplatin-based chemotherapy had improved activity against pancreatic ACC as compared to gemcitabine. Hashimoto et al [ 9 ] suggested that modified FOLFIRINOX was safe and effective in the treatment of pancreatic ACC.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the contribution of adjuvant chemotherapy and radiotherapy has not been well investigated. However, considering the available data, resection and adjuvant chemotherapy are associated with the longest rate of mOS, whereas in some cases, chemoradiation has shown activity in both the neoadjuvant and locally advanced settings[ 5 , 8 , 9 , 25 - 28 ].…”
Section: Accmentioning
confidence: 99%